PENGARUH PROFITABILITAS, STRUKTUR MODAL DAN KUALITAS LAPORAN KEUANGAN TERHADAP NILAI PERUSAHAAN - AMALIYAH, RIZKI (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
This study aims to examine the effect of profitability, capital structure and quality of financial reports on firm value. The research approach used in this research is a quantitative approach. The population in this study were all plantation sector companies listed on the Indonesia Stock Exchange. The sampling technique used in this study was Pupossive Sampling. This study used panel data regression analysis tools then continued to test the hypothesis with the help of Eviews 9.0 software. The results of this study show that profitability has no effect on firm value with a probability value of 0.3076> 0.05. Capital structure has no effect on firm value with a probability value of 0.1300> 0.05. The quality of financial statements has a significant effect on firm value with a probability value of 0.0144 <0.05. Then next. Simultaneously, profitability, capital structure and financial report quality have a significant influence on firm value, which can be shown by the Prob (F-Statistic) value of 0.021854 <0.05.